The Relationship between Midwifery Therapeutic Communication and the Level of Maternal Anxiety at the Babelan 1 Health Center, Babelan District, Bekasi Regency, West Java Province - Fitria (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Midwives who listen empathetically and provide clear and accurate explanations about the birth process, the actions to be taken, and provide the necessary emotional support, can help reduce the anxiety level of mothers in labor. Therefore, it is important for midwives to build a therapeutic communication relationship with birthing mothers to reduce the level of anxiety they feel. To determine the relationship between midwives' therapeutic communication and the level of anxiety of women giving birth at the Babelan 1 Community Health Center, Babelan District, Bekasi Regency, West Java Province, 202. The sample size in this study used a total of 30 pregnant women based on secondary data from the KIA poly room at Babelan 1 Community Health Center which was taken using total sampling. The sampling technique is non-probability sampling with a purposive method. The data used is primary data obtained from observations. The analytical method used is the normality test and the difference test (t test), namely the paired sample t test. There is a relationship between midwife's therapeutic communication and the level of anxiety of women giving birth at Babelan 1 Health Center, Babelan District, Bekasi Regency, West Java Province in 2024 with P-value < 0.005. It is hoped that midwives can apply therapeutic communication to reduce anxiety levels during the birthing process.